Immediate effects of different feedback methods on running jump height and motion improvement in male college basketball players - Soda, N.; Takayama, S.; Shimokochi, Y. (Human Movement Science, 2024)
The study aimed to assess the validity and accuracy of estimating running jump (RJ) height using the high-speed camera of a smartphone and to evaluate the effectiveness of oral and visual feedback via a smartphone in enhancing RJ movements and height in skilled athletes. Twenty male college basketball players were randomly assigned to either the Oral Feedback (OF) or Oral and Visual Feedback (OVF) group. Initially, participants performed RJs on force plates while being recorded with an iPhone (240 fps). Jump heights were estimated using the video, force plate data, and position data from pelvic markers (JHiPhone, JHFP, and JHRM, respectively). Subsequently, each group received tailored feedback based on the RJ video. After feedback, participants performed RJs again, and jump heights were re-estimated. The JHiPhone measurements were systematically higher but showed acceptable random errors compared to JHRM, with excellent reproducibility and strong positive correlations with JHFP and JHRM. Only the OVF group showed significant improvements in jump height post-feedback. Our results indicate that JHiPhone is a valuable and accurate tool for sports settings. Additionally, the results demonstrated that visual feedback using a smartphone is effective and should complement oral feedback to enhance RJ jump height in real sports settings.